Tracking the trajectories of international students' pragmatic choices in studying abroad in China: a social network perspective. Issue 4 (2nd October 2021) - Li, Citing; Li, Wendong; Ren, Wei
ABSTRACT: This paper reports on a longitudinal study that investigated how international students' personal network mediated their pragmatic choices during studying abroad in China. Data were collected over a year through different ways, including Study Abroad Network Questionnaire, role-plays, retrospective verbal reports, ethnographic interviews and observation field notes. Findings showed that with respect to pragmatic performance, the students exercised their subjectivity to converge to or diverge from the native-speaker norms. The ethnographic accounts revealed that the changes in learners' pragmatic choices were closely related to the composition and structure of their social network. Using two case learners, we highlighted that social network may work in synergy with pragmatic subjectivity to contribute to the trajectory changes over learners' socialisation processes. We discussed how social network may serve as both a theoretical lens and an analytical tool for investigating pragmatic development in study-abroad contexts.